2023
DOI: 10.1177/00220345221139230
|View full text |Cite
|
Sign up to set email alerts
|

Acute Postoperative Pain Due to Dental Extraction in the Adult Population: A Systematic Review and Network Meta-analysis

Abstract: This study compares the effectiveness of pharmacological treatments to develop guidelines for the management of acute pain after tooth extraction. We searched Medline, EMBASE, CENTRAL, and US Clinical Trials registry on November 21, 2020. We included randomized clinical trials (RCTs) of participants undergoing dental extractions comparing 10 interventions, including acetaminophen, nonsteroidal anti-inflammatory drugs (NSAIDs), opioids, and combinations to placebo. After duplicate screening and data abstraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…To date, we have assessed the certainty of evidence for the original version and the four updates of the living systematic review and NMA of randomised trials investigating the treatment of covid-19, which included more than 4000 comparisons in the latest version 9. Although the approach has not been formally tested yet, it has been successfully implemented in other systematic reviews with NMA 12131415…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, we have assessed the certainty of evidence for the original version and the four updates of the living systematic review and NMA of randomised trials investigating the treatment of covid-19, which included more than 4000 comparisons in the latest version 9. Although the approach has not been formally tested yet, it has been successfully implemented in other systematic reviews with NMA 12131415…”
Section: Discussionmentioning
confidence: 99%
“…We then developed a spreadsheet (supplementary file 1) that allowed automation of some steps and made modifications based on informal feedback from eight reviewers in charge of assessing the certainty of evidence in the living systematic review and NMA of randomised trials looking at the prophylaxis and treatment of covid-19. The approach was then successfully implemented in other four systematic reviews with NMA 12131415. This article describes practical strategies, including rule setting and automation that can facilitate implementation of the GRADE approach for NMA.…”
mentioning
confidence: 99%
“…A 2023 systematic review and network meta‐analysis of acute postoperative pain secondary to surgical tooth extraction by Miroshnychenko et al, concluded that the most effective oral pain management therapies were as follows: IBU 200 mg–400 mg plus APAP 500 mg–1000 mg; APAP 650 mg plus oxycodone 10 mg; and IBU 400 mg plus NAP 400 mg–440 mg. Oxycodone 5 mg, codeine 60 mg, or tramadol 37.5 mg plus APAP 325 mg, were no better than placebo. Opioids and their combinations were associated with higher rates of acute adverse events 48 …”
Section: Postoperative Analgesicsmentioning
confidence: 99%
“…The most valuable advantage for combining ibuprofen and APAP is the potential to improve analgesic efficacy without increasing the incidence of adverse drug reactions 48,57 …”
Section: Putting It All Together—post‐traumatic and Postsurgical Pain...mentioning
confidence: 99%
See 1 more Smart Citation